2020
DOI: 10.1186/s12913-020-05463-4
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a single point of access (SPA) to child and adolescent mental health services in England: a mixed-methods observational study

Abstract: Background: In many high-income countries, primary care practitioners are the main point of referral for specialist mental health services. In England, Child and Adolescent Mental Health Services (CAMHS) are increasingly adopting a Single Point of Access (SPA) to streamline referrals and introduce self and parent/carer-referrals. This involves a significant shift of responsibility from primary care towards CAMHS who adopt a more active role as gatekeeper for their service. This study evaluates the adoption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In both Bucks and Oxon, the numbers of people accessing SPA climbed quickly following initial awareness-raising activities [ 22 ]. While much of the emphasis on SPA was on the phone line, as the service evolved, increasing numbers of requests were received online, as described in more detail by Rocks et al [ 22 ] The introduction of the SPA was associated with an increase in self-referrals, both from carers and children and adolescents, and a fall in the proportion of referrals from primary care [ 22 ].…”
Section: Results (Including Refined Methods)mentioning
confidence: 99%
See 2 more Smart Citations
“…In both Bucks and Oxon, the numbers of people accessing SPA climbed quickly following initial awareness-raising activities [ 22 ]. While much of the emphasis on SPA was on the phone line, as the service evolved, increasing numbers of requests were received online, as described in more detail by Rocks et al [ 22 ] The introduction of the SPA was associated with an increase in self-referrals, both from carers and children and adolescents, and a fall in the proportion of referrals from primary care [ 22 ].…”
Section: Results (Including Refined Methods)mentioning
confidence: 99%
“…(Staff Interview) [22] "We are meant to do two days a week in SPA, but because we've had so many calls. .…”
Section: You Can Ring In At Any Time and You Can Just Be Reopened You Don't Need A Letter You Don't Need A Form You Don't Need Anybody Elmentioning
confidence: 99%
See 1 more Smart Citation
“…For families self-referral enabled them to bypass the barriers created by gatekeepers, while for practitioners self-referral enhanced the quality of referral information as this came directly from CYP and parents themselves. Other studies have similarly suggested that self-referral can overcome some of the access barriers CYP experience [ 17 , 44 47 ], although the role self-referral plays in improving the quality of referral information for practitioners has not been previously recognised. Self-referral is dependent on CYP/parents being aware of what services are available and the opportunity for self-referral.…”
Section: Discussionmentioning
confidence: 99%
“…Care and Department for Education 2017) and translated into a number of different strategies, including dramatic changes or 'Transformation' in child and adolescent mental health services (CAMHS) (Rocks et al 2020) as well as new initiatives to increase school-based provision and student-facing services (Wolpert M 2016). The school changes include encouraging schools to internally appoint a mental health lead as well as a new professional cohort of 'Educational Mental Health Practitioners' to provide early intervention and support to schools and pupils.…”
Section: These Have Been Heralded By Central Government (Department O...mentioning
confidence: 99%